Development of E-Module Discovery Learning Integrated Science Literacy by Kvisoft Flipbook Maker on Chemical Equilibrium - Lingga, Jeremi Ramon; Nainggolan, Bajoka (Universitas Negeri Medan, 2025)
Chemical equilibrium is an abstract concept illustrated by concrete examples requiring understanding of macro, submicroscopic, and symbolic levels and their interconnections. Observations at SMAN 2 Sidikalang show that learning still relies on textbooks, especially for chemical equilibrium, which limits student engagement and creativity due to minimal technology use. This research aims to obtain the development of an e-module Discovery Learning integrated science literacy by Kvisoft Flipbook Maker on chemical equilibrium to improve student learning outcomes and obtain positive responses from students. This research uses the type of Research and Development (R&D) using a 4D development model. The e-module developed was validated by material experts and media experts, consisting of 2 chemistry lecturers and 1 chemistry teacher. The results of this study are 1) The E-module was deemed highly valid, with average scores of 93.43% from material experts and 95.51% from media experts; 2) Students' response to the e-module was very positive with an average score percentage of 90.84%; 3) The increase in chemistry learning outcomes of students who are taught using e-modules is categorized as high marked by an N-Gain value of 0.84.